Pembentukan Return Saham Ekspektasian melalui Manajemen Laba di sekitar Peristiwa Pengumuman Program Opsi Saham Karyawan - Ida Bagus Putra Astika (Jurusan Manajemen Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2010)
This study discusses earning management issue around announcement of employees stock option plan (ESOP). ESOP represent a program aiming to give opportunity to employees specially executives to have company share by giving stock option, because employees have given service to company as a means to motivate employees specially executive improve based on performance. Explicitly, executives obliged to successfully apply ESOP, even though ESOP posits risk of losses and also contain opportunity to obtain return. Commitment to success, risk of lost and also opportunity to get this advantage push them to influence company share market price before and after announcement of ESOP through earning management. Through these ways, I found a mean to reduce potential loss and adversely obtain an advantage of stock option present around event of announcement of ESOP. The number of sample available is 38 companies. This sample is taken by purposive sampling of companies which adopting ESOP since 1999 up to 2007. Independent variable which is placed in model 1 and 2 is natural logarithms of stock option proportion, and an independent variable which placed in model 3 is discretionary accruals. Dependent variable for model 1, 2 and 3 is discretionary accruals. Discretionary accruals represent earnings management proxy. Hypotheses tested by using regression taking form of semi log regression for hypothesis 1 and 2 and simple regression (OLS) for hypothesis 3. The result indicates that executives conducting earning management by decreasing the amount of reported profit before announcement of ESOP and conduct earnings management by improving the amount of profit reported after announcement of ESOP. Result of the examination also indicates that conducted earnings management before announcement has a positive effect on earning management conducted after announcement of ESOP.Keywords: Employee Stock of Option Plan (ESOP), Earning Management and the Announcement.